A revision of the Neotropical nursery-web spider genus Architis (Araneae: Pisauridae) - Santos, Adalberto J. (Zootaxa, 2007)
The spider genus Architis Simon, 1898 is revised, resulting in sixteen species distributed from Panama to southern Brazil, all herein diagnosed, described and illustrated. Pisaurina brasiliensis Mello-Leitão, 1940 is transferred to Architis and considered a senior synonym of A. sinops Carico, 1989. The females of A. capricorna Carico, 1981 and A. robusta Carico, 1981 are described and illustrated for the first time. Architis nitidopilosa Simon, 1898 is considered a junior synonym of A. tenuis Simon, 1898 (the type species of the genus) and A. suarez Carico, 1989 a junior synonym of A. cymatilis Carico, 1981. The remaining species, A. ikuruwa Carico, 1981; A. tenuipes (Simon, 1898) and A. helveola (Simon, 1898) are redescribed and illustrated. Architis paulistana Mello-Leitão, 1917 is synonymised with Aglaoctenus lagotis (Holmberg, 1876) (Lycosidae: Sosippinae) based on its original description and type locality. Eight new species are described: A. erwini sp. nov., based on male and female specimens from Ecuador; A. comaina sp. nov. (male and female) and A. dianasilvae sp. nov. (female only) from Peru; A. maturaca sp. nov. (male and female) and A. altamira sp. nov. (female only) from Brazilian Amazonia; A. colombo sp. nov. (male and female), A. fritzmuelleri sp. nov. (female only) and A. turvo sp. nov. (female only) from southern and southeastern Brazil.